Hunting new animalcula with rare K and B decays - Buras Andrzej J. (EPJ Web of Conferences)
We summarize the recent strategy for an efficient hunting of new animalcula with the help of rare K and B decays that avoids the use of the |Vcb| and |Vub| parameters that are subject to tensions between their determinations from inclusive and exclusive decays. In particular we update the values of the |Vcb|-independent ratios of various K and B decay branching ratios predicted by the Standard Model. We also stress the usefulness of the |Vcb|–γ plots in the search for new physics. We select the magnificant seven among rare K and B decays that should play a leading role in the search for new physics due to their theoretical cleanness: B+ → K+(K*)vv- and K+ → π+vv- measured recently by Belle II and NA62, respectively, KL → π0vv- investigated by KOTO and also Bs,d → μ+μ− and KS → μ+μ− measured by the LHCb, CMS and ATLAS experiments at CERN.